The Effect of Treagust Model in Acquiring Rhetorical Concept for Literary Fifth Year Female Students and Developing Their Effective Communication - Rasheed, Nedal Muzahim; Kurdi, Kholoud Aziz (Journal of Tikrit University for Humanities, 2022)
This research aims to identify the effect of the Treagust model on acquiring rhetorical concepts for fifth-grade literary students and developing their ability to communicate effectively. In order to achieve the research aims of the study, the researcher developed three hypotheses: 1- There is no statistically significant difference at the level of (05.0) between the average scores of students of the experimental group who are studying rhetoric and application according to the Treagust model and the average scores of students of the control group who study rhetoric and application according to the usual (traditional) method, in a test Concept acquisition. 2- There is no statistically significant difference at the level (05.0) between the average scores of the experimental group who are studying rhetoric and application according to the Treagust model and the average scores of students of the control group who are studying rhetoric and application according to the usual (traditional) method in the scale of effective communication. 3- There is no statistically significant difference at the level (05, 0) between the average differences between the degrees of students of the experimental group who are studying rhetoric and application according to the Treagust model in the pre and post scale for effective communication. The two researcher adopted the experimental design with partial control of the two experimental and control group , and the researcher sample consisted of (50) student who were intentionally selected from AL- ALam and AL- HiKma schools. A test was made for acquiring rhetorical concepts, which included (24) test clauses of a multiple choice type that measures the three processes for acquiring rhetorical concepts and it was ascertained its validity, difficulty in its paragraphs, its ease, distinction and consistency, while the second means was represented by an effective communication test that will be in its final form of (40) Paragraph, honesty, distinction, and consistency were calculated for this measure, and after data was collected and statistically processed and using the for two independent samples.